Feasibility of bulk shipping investments – investment into the handysize segment with time horizon between 2021 and 2027 - Hong, Brian (Nanyang Technological University, 2022)
To acquire capital, shipping companies must show that they are able to create value for their shareholders. Therefore, the basis for any investors’ decision to invest comes from understanding and deriving the value of a particular asset. Hence, this volume seeks to compare the value of different investment strategies available when investing in the Handysize segment and identifying the most optimal strategy to perform.